PELATIHAN DASAR SPMI DAN AMI UNTUK MENINGKATKAN PEMAHAMAN PENGGERAK SPMI PERGURUAN TINGGI - Suharyanti, Yosephine; Purwanugraha, Heribertus Andre; Handoko, Luky; Emanuel, Andi Wahju Rahardjo; Bharata, Bonaventura Satya; Vitasurya, Vincentia Reni; Rudwiarti, Lucia Asdra; Budiharta, Pratiwi; Pramudyanto, Alexander Beny; Wiranata, F. Edwin (Universitas Negeri Surabaya, 2025)
Internal quality assurance (IQA) in higher education institutions (HEIs) is believed to be the spearhead for accelerating the improvement of the quality of HEIs and the study programs within it. However, currently many HEIs are trapped in the formal implementation of IQA and does not reach its essence, so it does not have a real impact on the quality of the HEIs. Universitas Atma Jaya Yogyakarta is one of the partners of the Directorate of Learning and Student Affairs of the Directorate General of Higher Education, Research, and Technology to devote itself by providing training and sharing good practices in implementing IQA to six HEIs with 31 study programs in 2024. This training aims to provide experience and insights for participants to become drivers of accelerating the implementation of IQA in their respective HEIs and study programs. The training was carried out in two stages in September and October 2024, each for two days, with materials covering IQA system development, IQA organization, IQA documents, and internal quality audits. This training went smoothly and effectively, as evidenced by the increase in participants' comprehension as measured by a pre-test and a post-test. After six months had passed, the indirect impact of this training was also seen in the accreditation of two participating HEIs that had unaccredited status during the training.